Lukács: estranhamento, ética e formação humana - Lopes, Fátima Maria Nobre (2006)
This work, based on Lukács’ theory in The Ontology of Social Being, is conducted under the analysis of the strangement (“Entfremdung”) phenomenon in capitalism, which is a barrier to the full human genus explicitation, and its overcoming through ethics. In this approach we detach the strangement genesis in the labour process, which presents itself under the form of fetishism of commodities, that takes place in various social aspects of human life. Yet we evidence the ontological distinction between the words alienation (Entäusserung) and strangement (Entfremdung), which are not differentiated in english translations, known simply as “alienation”. We discuss the necessity and possibility of the overcoming of strangement, performed by men themselves when they acquire the conscience that they are part of the human genus, going away from their particularity, their in-itself, and evolving to a for-itself stage. In the discussion of these subjects we recall central elements of Lukács’ Ethics found in the Ontology, mainly referring to the ontological constitution of values and of the must-be. We also refute the idea of a general teleology as men’s conscious activities in the self-construction process are affirmed, which result in the formation of the human genus. From all these questions we come up with the thesis that whatever it is the way and the subject to strangement overcoming, an ethical education is necessary, that is, the formation of a conscience that understands how strangement develops and that really wants to fight it. This formation must have an ethic intercession, otherwise the fighters will remain in their particularism, hardening the convergence between the self and the alterity and, consequently, blocking the true human emancipation.